Analisis Tindak Tutur Direktif Podcast Youtube Gita Wirjawan Episode Kecerdasan dan Kebahagiaan dalam Perspektif Neurosains - Mutmainna, Nurul; Azis, Azis; Agussalim, Andi (Nuances of Indonesian Language, 2025)
This study is a qualitative study that aims to describe the types of directive speech acts in Gita Wirjawan's podcast episode "happiness and intelligence from a neuroscience perspective", and to describe the functions of directive speech acts in Gita Wirjawan's podcast episode "happiness and intelligence from a neuroscience perspective". This study is a type of qualitative research with a descriptive method. The data in the study are in the form of dialogues in Gita Wirjawan's YouTube podcast. The data in this study were collected through literature studies, documentation techniques and note-taking techniques. The results of this study indicate that there are five types of directive speech acts, namely: types of requests (requestives), types of questions (questions), permission (permissive) and advice (advisories), types of prohibite.